ORGANIZATIONAL COMMITMENT AND PERFORMANCE OF LECTURERS IN STRUCTURAL MODEL: LEADERSHIP, COMPETENCE AND COMMUNICATION - Prasetyaningrum, Dina; Rachmawati, Indra; Yogawati, Nursanti Dwi (AIBPM Publisher, 2023)
When an organization's performance necessitates the consequences of collaboration between individual performance and affected components, it is considered to be successful and effective. Each administrator's potential is taken into account when dividing management duties into different categories, and all members and the leadership place their trust in them. One of the case studies that can be seen is the education system in Indonesia, specifically the universities, where the performance of lecturers and their leadership, communication, and competency are key factors in determining student achievement. The accomplishment of lecturers in carrying out the execution of instruction, research, and community service is demonstrated by a competent graduate student (Tri Dharma of Higher Education). Using SEM PLS, a quantitative research methodology was applied. Saturation sampling was used in a quantitative study that included all 122 lecturers who responded to questionnaires at the Universities of Al-Irsyad Cilacap and Nahdlatul Ulama Al Ghazali Cilacap. The results of the analysis revealed that, with P values less than 0.05, leadership, competence, communication, and organizational commitment have a substantial impact on lecturer performance. Leadership, in the meantime, can affect performance through the supplementary factor of organizational commitment.